2005
DOI: 10.1007/11554714_5
|View full text |Cite
|
Sign up to set email alerts
|

Likely Scenarios of Intron Evolution

Abstract: Abstract. Whether common ancestors of eukaryotes and prokaryotes had introns is one of the oldest unanswered questions in molecular evolution. Recently completed genome sequences have been used for comprehensive analyses of exon-intron organization in orthologous genes of diverse organisms, leading to more refined work on intron evolution. Large sets of intron presence-absence data require rigorous theoretical frameworks in which different hypotheses can be compared and validated. We describe a probabilistic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…The next generation of increasingly sophisticated ML reconstructions of intron gain and loss during eukaryotic evolution suggested that the protein-coding genes of ancient eukaryotic ancestors, including the Last Eukaryotic Common Ancestor (LECA), already possessed intron density comparable to that found in modern, moderately intron-rich genomes [85-88,136]. Accordingly, the history of eukaryotic genes, with respect to the dynamics of introns, appears to be to a large extent dominated by losses, perhaps punctuated by a few episodes of major gain [87,88,91,137].…”
Section: Reconstruction Of Evolution Of Exon-intron Structure Of Eukamentioning
confidence: 99%
See 1 more Smart Citation
“…The next generation of increasingly sophisticated ML reconstructions of intron gain and loss during eukaryotic evolution suggested that the protein-coding genes of ancient eukaryotic ancestors, including the Last Eukaryotic Common Ancestor (LECA), already possessed intron density comparable to that found in modern, moderately intron-rich genomes [85-88,136]. Accordingly, the history of eukaryotic genes, with respect to the dynamics of introns, appears to be to a large extent dominated by losses, perhaps punctuated by a few episodes of major gain [87,88,91,137].…”
Section: Reconstruction Of Evolution Of Exon-intron Structure Of Eukamentioning
confidence: 99%
“…Episodes of substantial intron gain seem to coincide with the emergence of major new groups of organisms with novel biological characteristics such as the Metazoa (Figure 7) [53]. Several previous studies, performed on much smaller data sets and with less robust reconstruction methods, have suggested that at least some eukaryotic ancestral forms could have possessed intron-rich genes [84,85,136], and observations on gene structures in primitive animals such as the sea anemone Nematostella [139] and the flatworm Platynereis [140] were compatible with these inferences. A particularly striking conclusion has been reached in the reconstruction of the evolution of gene architecture in Chromalveolata: although all sequenced genomes in this supergroup of eukaryotes are intron-poor, intron-rich last common ancestors have been inferred for Chromalveolata and particularly Alveolata [141].…”
Section: Reconstruction Of Evolution Of Exon-intron Structure Of Eukamentioning
confidence: 99%
“…Avariety of studies have shown that genes from intron-rich species from any major eukaryotic supergroup share a significant number of intron positions with other groups (Fedorov et al 2002;Rogozin et al 2003;Csurös et al 2008Csurös et al , 2011. Different investigators have used different methods of evolutionary inference, ranging from parsimony to maximum likeli-hood, to attempt to reconstruct ancestral intron densities (Rogozin et al 2003;Qiu et al 2004;Csurös 2005Csurös , 2008Nguyen et al 2005;Roy and Gilbert 2005;Carmel et al 2007Carmel et al , 2009). With increasing taxonomic sampling usually yielding increasingly higher estimates for LECA's intron density, the latest reconstructions (Csurös et al 2011) used a Markov chain Monte Carlo approach to investigate 99 genomes from five eukaryotic supergroups, and estimated that LECA had 53% -74% of modern human intron density, or 4.5 -6.3 introns per gene (assuming similar average protein-coding lengths).…”
Section: Reconstruction Of Intron-exon Structures In Lecamentioning
confidence: 99%
“…Consequently, likelihood methods tend to underestimate the extent of gene losses. The situation is similar to what is encountered in likelihood models of intron evolution and a possible remedy is discussed in (Csűrös 2005). This paper focuses on the core algorithmic problems of likelihood computations in a biologically realistic model of gene content evolution.…”
Section: Resultsmentioning
confidence: 83%